An Analysis of Students’ Ability in Retelling Narrative Text in Written Form - S, Kartika (English Education: Jurnal Tadris Bahasa Inggris, 2017)
The objective of this research is to know how good the students’ ability in developing generic structure of retelling narrative text in written form in Senior High School. The research methodology used in this research is Descriptive Research. The result is used to know how good the students’ ability in retelling narrative text in written form which was focused in organization of narrative text. This research was conducted at MAN 1 Bandar Lampung. The sample was chosen X 5 based on the data of students’ score that is the lowest score of all classes. In collecting the data, this research used test instrument. Test instrument was written test. There are four steps for analyzing students’ ability: Assessing the students’ writing, making tabulation, finding the total average score of all students, and finding the percentage each classification of students’ score. From the data analysis, it was found the total average score of all the students in retelling narrative text shown 14 of score. If that score is classified, it is good to average score classification. If the score of each classification was put into percentage, it was found 32.26% students who got excellent to very good score classification, 41.93% students who got good to average, 9.68% students who got fair to poor score classification and 16.13% students who got very poor score classification. The highest frequency score classification of the students’ ability in organization is good to average score classification with 41.93%.